The acute effects of combined supplementation of beta-alanine, carbohydrate and whey protein on biochemical parameters of athletes after exhaustive exercise - Mor, Ahmet; İpekoğlu, Gökhan and Arslanoğlu, Erkal and Arslanoğlu, Cansel and Acar, Kürşat (Progress in Nutrition, 2018)
Background: The beneficial effect of popular supplements and use of combined supplementation in athletes which purpose to increase sports performance. Objective: This study aimed to review biochemical responses that the athletes gave to combined supplementation received after exercise and some changes in hematological values. Material and Method: 16 volunteers, in shape, male athletes with ages between 18-25 participated into the study. Athletes were divided into two groups as experiment (supplement) (n=8) and control (placebo) (n=8). After the exercise made until exhaustion (shuttle run test), beta-alanine/vitargo(carbohydrate-electrolyte)/whey protein supplement was given to the experimental group while the control group received placebo (water). Blood was taken from the athletes three times as basal, post-exercise (PE) and 2 hours after ingestion supplement (PS); Urea, Creatinine, Cholesterol, Triglyceride, High Density Lipoprotein (HDL), Low Density Lipoprotein (LDL), Gamma Glutamyl Transferase (GGT) and Alkaline Phosphatase (ALP) values have been analyzed. Results: Statistically significant differences in many biochemical parameters were found when comparisons of in-group basal, PE and PS time courses of supplement and control groups were reviewed (p<0.05). When inter-group comparison of triglyceride and cholesterol levels were reviewed, a significant difference was seen in basal levels (p<0.05) no difference was detected in values other than that (p>0.05). Conclusions: It is possible to say that acute combined supplementation used after exercise does not create a negative effect on biochemical parameters of athletes, on the contrary when the research result data were compared with control group, by looking at the basal, exercise and after supplementation values such as creatinine, cholesterol, triglycerides, HDL and LDL, the combined supplement intake showed positive results in terms of health.